Chemical constituents and ACE inhibitory activity of desert plant Suaeda physophora Pall. - Ruizhi Men; Ning Li; Yachao Xing; Yingzhan Tang; Chengyu Tan; Fantong Meng; Juan Zhang; Hui Ni; Xiaoguang Jia (Elsevier, 2013)
Suaeda physophora Pall. is a kind of desert plant mostly growing in saline habitats in Xinjiang Uygur Autonomous Region. In order to have a better utilization of halophytes, a screening for ACE inhibitors from halophytes growing in Xinjiang was carried out. The result showed that the 70% EtOH extract and n-BuOH extract of S. physophora Pall. possessed significant ACE inhibitory activities. So we focused on its biochemical constituents firstly. One new quinazoline alkaloid, namely Suaedine (1), along with six known compounds (2-7) was isolated from the aerial parts of S. physophora Pall. The structure of the new quinazoline alkaloid was established by one- and two-dimensional nuclear magnetic resonance, optical rotation and mass spectrometry analysis. The flavonoid compounds (2-4) and phenolic compound (5) exhibited significant ACE activities. It was the first time to focus on the chemical constituents and bioactivities of this plant.